Effect of Adding Chelating Agents on the Absorption of Zinc from Polluted Soil Sludge Textile Industrial Waste by Sunflower Plant (Helianthus annuus L.) - Ruslan Wirosoedarmo; F. Anugroho; S. D. Hanggara; Kiki Gustinasari (Applied and Environmental Soil Science)
Textile industry caused the increase of the heavy metal Zn in soil in the form of sludge. Waste treatment by the phytoremediation method is one of the alternatives of environmental refinement with low cost and high effectiveness. This study used sunflower plants (Helianthus annuus L.) as a phytoremediator. The chelating agent EDTA was added in some treatment to increase the heavy metal absorption. The addition of 1.5 kg sludge on growth media inhibits the sunflower growth. T0K0 treatment has the most efficient result with a total Zn absorption of 101.74 mg/kg. T0K0 treatment was able to reduce Zn up to 96%. In 100% soil treatment, the EDTA additions decreased the ability of sunflower plants to absorb Zn metal in the phytoremediation process. However, in the 40% sludge treatment, the addition of EDTA did not affect the ability of sunflower plants to absorb the Zn metal in the phytoremediation process.